THE DILEMMA OF SINGLE WOMEN: THE CONCEPT OF KAFĀ'AH IN ISLAMIC JURISPRUDENCE AND THE COMPILATION OF ISLAMIC LAW - Ulfa Safira Soliha; M. Syahnan; Muhammad Iqbal Irham (Program Pascasarjana UIN Sumatera Utara, 2026)
The modern world, which provides women with the freedom to pursue the highest possible education, can also have negative impacts on them. Modern women with higher education often face challenges in finding partners due to the concept of equality (kafaah). This study aims to analyze the concept of kafaah in Islamic jurisprudence (Fiqh) and the Compilation of Islamic Law and its relevance to the phenomenon of highly educated women remaining single for extended periods. This study employed a qualitative method with a library research approach, analyzing various literature such as fiqh books, scientific journals, and laws and regulations. The results show that in Islamic law, kafaah is not a requirement for a valid marriage, but rather a social consideration to maintain household harmony, with the primary benchmarks being religious and moral aspects. Differences in social, economic, or educational status cannot be used as a reason to hinder marriage. However, in social reality, the understanding of kafaah often shifts in meaning due to patriarchal culture and materialistic perceptions, so that highly educated women are often considered difficult to find a